Bromelain: an overview of industrial application and purification strategies - Mohd Arshad, Zatul Iffah; Amid, Azura; Yusof, Faridah; Jaswir, Irwandi; Ahmad, Kausar; Loke, Show Pau (Springer-Verlag Berlin Heidelberg, 2014)
Abstract This review highlights the use of bromelain in various applications with up-to-date literature on the purification of bromelain from pineapple fruit and waste such as peel, core, crown, and leaves. Bromelain, a cysteine protease, has been exploited commercially inmany applications in the food, beverage, tenderization, cosmetic, pharmaceutical, and textile industries. Researchers worldwide have been directing their interest to purification strategies by applying conventional and modern approaches, such as manipulating the pH, affinity, hydrophobicity, and temperature conditions in accord with the unique properties of bromelain. The amount of downstream processing will depend on its intended application in industries. The breakthrough of recombinant DNA technology has facilitated the large-scale production and purification of recombinant bromelain for novel applications in the future.